Implementation of Uterine Artery Doppler Scanning: Improving the Care of Women and Babies High Risk for Fetal Growth Restriction - Emmanuel Ekanem; Faris Karouni; Emmanuoil Katsanevakis; Habiba Kapaya (Journal of Pregnancy)
Introduction. While stillbirth rates have declined in many countries, these declines are less marked in the UK. Fetal growth restriction (FGR) affects about 3% to 7% of all pregnancies and is by far the single strongest risk factor for stillbirth. FGR implies a pathological restriction of the genetic growth potential and is not synonymous with small-for-gestational age (SGA). The Royal College of Obstetricians and Gynaecologists (RCOG) defines SGA as an estimated fetal weight (EFW) or abdominal circumference (AC) less than the 10th centile. The likelihood of FGR is higher in severe SGA defined as an EFW or AC less than the 3rd centile. The second version of Saving Babies’ Lives Care Bundle (SBLCBv2) recommends the second trimester uterine artery Doppler (UtAD) pulsatility index (PI) screening for pregnancies at high risk of FGR. This study was aimed at determining the prevalence of FGR and assess pregnancy outcomes following the implementation of UtAD at the United Lincolnshire Hospitals NHS Trust (ULHT). Methods. One-year retrospective cohort study (1st September 2020-31st August 2021) was conducted across both ULHT hospitals in the UK (Lincoln County Hospital in Lincoln and Pilgrim Hospital in Boston). Results. During the study period, 5197 women were booked at ULHT. Of 5197, 349 were identified as high risk for FGR. When numbers were compared for the two hospitals, FGR rate was higher in Lincoln 8.10% vs. 4.51% in Boston. In addition, an increased proportion of abnormal UtAD scans was observed in Lincoln (35.7%) vs. in Boston (22%) (P=0.014). Of the 349 UtAD scans, 237 were normal (67.9%), 41 showed unilateral notching (11.7%), 43 bilateral notching (12.3%), and 28 raised PI (8%). Babies in the bilateral notching group exhibited the lowest birth weight (P=0.005), born at an earlier gestation (P=0.029), and with low Apgar scores at 1 (P=0.007) and 5 minutes (P<0.001). Discussion. UtAD is a useful second trimester screening tool for women identified as high risk for FGR and helps stratify the intensity of surveillance. However, the findings call into question a focus solely on the UtAD PI for improving FGR detection without taking into account bilateral notching.